Therapeutic expression of human clotting factors IX and × following adeno‐associated viral vector‐mediated intrauterine gene transfer in early‐gestation fetal macaques. Issue 3 (5th December 2018) - Chan, Jerry K. Y.; Gil-Farina, Irene; Johana, Nuryanti; Rosales, Cecilia; Tan, Yi Wan; Ceiler, Jessika; Mcintosh, Jenny; Ogden, Bryan; Waddington, Simon N.; Schmidt, Manfred; Biswas, Arijit; Choolani, Mahesh; et al.
ABSTRACT: Adeno‐associated viral vectors (AAVs) achieve stable therapeutic expression without long‐term toxicity in adults with hemophilia. To avert irreversible complications in congenital disorders producing early pathogenesis, safety and efficacy of AAV‐intrauterine gene transfer (IUGT) requires assessment We therefore performed IUGT of AAV5 or ‐8 with liver‐specific promoter‐1 encoding either human coagulation factors IX (hPIX) or × (hFX) into Macaca fascicularis fetuses at ∼0.4 gestation. The initial cohort received 1 × 10 12 vector genomes (vgs) of AAV5‐hFIX ( n = 5; 0.45 × 10 13 vg/kg birth weight), resulting in ∼3.0% hPIX at birth and 0.6–6.8% over 19–51 mo. The next cohort received 0.2‐1 × 10 13 vg boluses. AAV5‐hPX animals ( n = 3; 3.57 × 10 13 vg/kg) expressed <1% at birth and 9.4–27.9% up to 42 mo. AAV8‐hFIX recipients ( n = 3; 2.56 × 10 13 vg/kg) established 4.2–41.3% expression perinatally and 9.8–25.3% over 46 mo. Expression with AAV8‐hFX ( n = 6, 3.12 × 10 13 vg/kg) increased from <1% perinatally to 9.8–13.4% >35 mo. Low expressers (<1%, n = 3) were postnatally challenged with 2 × 10 11 vg/kg AAV5 resulting in 2.4–13.2% expression and demonstrating acquired tolerance. Linear amplification‐mediated‐PCR analysis demonstrated random integration of 57–88% of AAV sequences retrieved from hepatocytes with no events occurring in or near oncogenesis‐associated genes. Thus, early‐IUGT in macaques produces sustained curative expression related significantly to integrated AAV in the absence of clinical toxicity, supporting its therapeutic potential for early‐onset monogenic disorders.—Chan, J. K. Y., Gil‐Farina I., Johana, N., Rosales, G., Tan, Y. W., Ceiler, J., Mcintosh, J., Ogden, B., Waddington, S. N., Schmidt, M., Biswas, A., Choolani, M., Nathwani, A. G., Mattar, C. N. Z. Therapeutic expression of human clotting factors IX and × following adeno‐associated viral vector‐mediated intrauterine gene transfer in early‐gestation fetal macaques. FASEB J. 33, 3954–3967 (2019). www.fasebj.org